(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of smartphone technology has given birth to a new visual culture, making digital photography a crucial competency for the existence and creativity of the younger generation in social media. This community service aims to improve the photography skills of students of SMA Negeri 8 Garut through the use of artificial intelligence (AI). The activity was carried out using an educational mentoring method that focused on basic techniques (Composition, lighting, angles and optimization of AI features. The evaluation results showed that the program was effective, where the majority of participants achieved a good level of understanding of basic techniques (21% very understanding, 50% understanding, 26.6% quite understanding) and the use of AI features (35.7% very understanding, 64.3% understanding). Overall, this training succeeded in becoming an initial provision for developing students’ economic potential in the field of photography, although the in-depth study on aspects of manual camera settings and low-level techniques light still needs improvement in the future.